Chitosan scaffolds containing calcium phosphates and diclofenac for bone regeneration – Development, validation and optimization - Neves, Lara Mariana Almeida Duarte Das (2019)
Tese de mestrado, Ciências Biofarmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2018